2016
DOI: 10.1136/oemed-2016-103648
|View full text |Cite
|
Sign up to set email alerts
|

Does aircraft noise exposure increase the risk of hypertension in the population living near airports in France?

Abstract: These findings contribute to the overall evidence suggesting that aircraft noise exposure at night-time may increase the risk of hypertension in men. Hypertension is a well-known and established risk factor for cardiovascular disease. The association reported in the present study between aircraft noise and hypertension implies that aircraft noise might be a risk factor also for cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 19 publications
7
60
0
Order By: Relevance
“…The DEBATS main study found a significant association between night-time aircraft noise exposure and the risk of hypertension in men only 12. In this study, comparisons between men and women to ascertain whether sex steroids or menopausal status would influence HPA axis, showed no gender differences for the association between cortisol levels or variation and noise exposure.…”
Section: Discussionmentioning
confidence: 42%
“…The DEBATS main study found a significant association between night-time aircraft noise exposure and the risk of hypertension in men only 12. In this study, comparisons between men and women to ascertain whether sex steroids or menopausal status would influence HPA axis, showed no gender differences for the association between cortisol levels or variation and noise exposure.…”
Section: Discussionmentioning
confidence: 42%
“…Many studies have demonstrated the adverse effects of exposure to aircraft noise on health, such as annoyance [5,6], sleep disturbance [7,8], cardiovascular diseases including hypertension [9,10,11,12,13], and alteration of cognitive performances among children [14,15]. The association between noise exposure and noise annoyance has been extensively investigated, and aircraft noise has been found to be the most annoying noise source among all transportation noise sources when standardized for noise exposure level [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evidenced adverse effects of exposure to aircraft noise on health: altered cognitive performance, annoyance, sleep disturbance, hypertension and cardiovascular diseases [1]- [5]. Some studies support the hypothesis that psychological aspects such as noise annoyance play an important role in the association between environmental noise and adverse effects on health [6].…”
Section: Methodsmentioning
confidence: 93%